2018
DOI: 10.3390/jcm7090266
|View full text |Cite
|
Sign up to set email alerts
|

Translational Medicine in Pulmonary-Renal Crosstalk: Therapeutic Targeting of p-Cresyl Sulfate Triggered Nonspecific ROS and Chemoattractants in Dyspneic Patients with Uremic Lung Injury

Abstract: Molecular mechanisms and pathological features of p-Cresyl sulfate (PCS)-induced uremic lung injury (ULI) in chronic kidney disease (CKD) remain unclear. We analyzed pleural effusions (PE) from CKD and non-CKD patients for uremic toxins, reactive oxygen species (ROS), and chemotactic cytokines. Correlations between PE biomarkers and serum creatinine were also studied. Cell viability and inflammatory signaling pathways were investigated in PCS-treated human alveolar cell model. To mimic human diseases, CKD-ULI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The involvement of mitochondrial ROS formation in this process was proven by lower NADPH activity in Gpx1 overexpressing mice and higher NADPH activity in Gpx1 knockout mice. A cross talk between mitochondria and NOX1 or NOX2 was also shown for cellular starvation [152], nitrate tolerance [140], the aging process [79,82,139,153], AGE/RAGE signaling [154], endotoxemia as a model of sepsis [155], dyspneic patients with uremic lung injury [156], AsO 3 toxicity [157], idiopathic pulmonary fibrosis [158], and tumorigenesis [159]. Even a triple cross talk between NOX4, NOX2, and mitochondria as well as ROS-induced ROS release was described in vascular endothelial growth factor (VEGF) signaling and angiogenesis [160].…”
Section: Cross Talk Between Different Sources Of Ronsmentioning
confidence: 86%
“…The involvement of mitochondrial ROS formation in this process was proven by lower NADPH activity in Gpx1 overexpressing mice and higher NADPH activity in Gpx1 knockout mice. A cross talk between mitochondria and NOX1 or NOX2 was also shown for cellular starvation [152], nitrate tolerance [140], the aging process [79,82,139,153], AGE/RAGE signaling [154], endotoxemia as a model of sepsis [155], dyspneic patients with uremic lung injury [156], AsO 3 toxicity [157], idiopathic pulmonary fibrosis [158], and tumorigenesis [159]. Even a triple cross talk between NOX4, NOX2, and mitochondria as well as ROS-induced ROS release was described in vascular endothelial growth factor (VEGF) signaling and angiogenesis [160].…”
Section: Cross Talk Between Different Sources Of Ronsmentioning
confidence: 86%
“…We previously reported that intracellular sources of ROS induced by PCS are multifaceted, including NADPH oxidase and mitochondria [8]. Our prior findings elucidated single inhibitors for NADPH oxidase-derived ROS and mitochondria-targeted superoxide could not abrogate downstream inflammatory responses to attenuate cell damages, reflecting the underlying signaling transduction network is intricate.…”
Section: Discussionmentioning
confidence: 98%
“…The representative protein-bound uremic toxins (PBUT), p-cresyl sulfate (PCS) and indoxyl sulfate (IS), exert pro-oxidant and pro-inflammatory effects on diverse cell and organ systems [8,9] PCS mainly presents as a protein-bound form in the blood circulation, and this study is focusing on the free form of PCS [10]. Experimental data from cell and animal models suggest that reactive oxygen species (ROS) and chronic sustained inflammation resting from circulating PTUB are hallmarks of UVC and capable of pivotal inducers of osteogenesis in human arterial smooth muscle cell (HASMC) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, excess nitric oxide production may result in peroxynitrite production, endothelial damages, and neuron injuries, a process referred to as nitrosative stress (28,29). Meanwhile, the burden of pro-inflammatory and pro-oxidant state is reminiscent of uremic milieu in chronic kidney disease (30). In light of this, ESRD patients superimposed on DM would be at the greatest risk of impaired CSR related death.…”
Section: Resultsmentioning
confidence: 99%